Malseating of modular dual mobility liners. (15th October 2021) - Guntin, Jonathan; Plummer, Darren; Della Valle, Craig; DeBenedetti, Anne; Nam, Denis
Abstract : Aims: Prior studies have identified that malseating of a modular dual mobility liner can occur, with previous reported incidences between 5.8% and 16.4%. The aim of this study was to determine the incidence of malseating in dual mobility implants at our institution, assess for risk factors for liner malseating, and investigate whether liner malseating has any impact on clinical outcomes after surgery. Methods: We retrospectively reviewed the radiographs of 239 primary and revision total hip arthroplasties with a modular dual mobility liner. Two independent reviewers assessed radiographs for each patient twice for evidence of malseating, with a third observer acting as a tiebreaker. Univariate analysis was conducted to determine risk factors for malseating with Youden's index used to identify cut-off points. Cohen's kappa test was used to measure interobserver and intraobserver reliability. Results: In all, 12 liners (5.0%), including eight Stryker (6.8%) and four Zimmer Biomet (3.3%), had radiological evidence of malseating. Interobserver reliability was found to be 0.453 (95% confidence interval (CI) 0.26 to 0.64), suggesting weak inter-rater agreement, with strong agreement being greater than 0.8. We found component size of 50 mm or less to be associated with liner malseating on univariate analysis (p = 0.031). Patients with malseated liners appeared to have no associated clinical consequences, and none required revision surgery at a mean of 14 months (1.4 to 99.2) postoperatively. Conclusion: The incidence of liner malseating was 5.0%, which is similar to other reports. Component size of 50 mm or smaller was identified as a risk factor for malseating. Surgeons should be aware that malseating can occur and implant design changes or changes in instrumentation should be considered to lower the risk of malseating. Although further follow-up is needed, it remains to be seen if malseating is associated with any clinical consequences. Cite this article: Bone Jt Open  2021;2(10):858–864.